Method for the synthesis of para‐aramid nanofibers. Issue 42 (15th July 2016) - Yeager, Matthew P.; Hoffman, Christopher M.; Xia, Zhiyong; Trexler, Morgana M.
ABSTRACT: The synthesis and electrospinning of novel N ‐substituted aramid nanofibers (ANFs) prepared from basic dispersions of commercial microscale Kevlar fibers are herein reported. The functionalized ANFs were characterized via Fourier transform infrared spectroscopy, 13 C solid‐state nuclear magnetic resonance spectroscopy, and X‐ray diffraction to confirm proper N ‐substitution of the side groups and to determine changes to the polymer crystallinity and stability. These analyses suggested that the electrospun ANFs consisted of numerous crystalline domains in the transverse fiber direction with large amorphous regions that were void of defects commonly found in commercial Kevlar fibers. A semi‐empirical study of the variations in the solubility parameter due to various side chain moieties was conducted to facilitate solvent selection and to elucidate the enhanced solubility effects with selected organic solvents. These initial findings suggest a promising route for obtaining a new class of nanofibers with ultrahigh strength and stiffness. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44082. Abstract :